Theokrasi dalam Kitab Daniel dan Relevansinya dengan Karakter Kepemimpinan Modern - Sheren Angelina Lumintang; Sheline Feranda Lumintang (Sekolah Tinggi Teologi Injili Indonesia (STTII) Yogyakarta, 2026)
Crises of integrity, abuse of power, and a lack of ethical leadership pose serious challenges to modern leadership. In this context, the Book of Daniel offers a relevant theological perspective for the development of leadership characterised by integrity and accountability. This study examines the concept of God’s theocracy in the Book of Daniel and its implications for modern leadership. The Book of Daniel presents various events that affirm God’s sovereignty over human government, including the experiences of Daniel and his companions in the Babylonian exile, Nebuchadnezzar’s dream, and the downfall of Belshazzar. These stories demonstrate that true leadership is not based solely on worldly power, but is also subject to divine authority. The key principles drawn from the Book of Daniel include integrity, wisdom, steadfast faith, and reliance on God in decision-making. In the context of modern leadership, this study demonstrates that the principles of God’s theocracy in the Book of Daniel remain relevant in shaping ethical leadership grounded in moral values. The novelty of this research lies in the reinterpretation of the concept of theocracy as a biblical-ethical framework for modern leadership, particularly in addressing ethical crises, the abuse of power, and moral dilemmas. The values exemplified by Daniel serve as a guide for leaders in building leadership that is just and oriented towards the common good. This research is a literature review employing a theological-biblical approach and narrative analysis of the Book of Daniel to identify leadership principles and their relevance in a modern context. The results of the study indicate that the Book of Daniel presents three main principles of leadership, namely moral integrity, an awareness of transcendent authority, and ethical courage under political pressure. These findings demonstrate the relevance of biblical leadership principles to the practice of modern, ethical and responsible leadership.